Lipoxygenase regulation in vivo and in vitro by lipid compounds - Skaterna, T.D.; Kopich, V.M.; Kharitonenko, G.I.; Kharchenko, O.V. (Вiopolymers and Cell, 2015)
Lipoxygenases (LOs) are known as one of the enzymes of lipid peroxidation. The majority of LOs are soluble enzymes and have affinity to membranes. The enzyme translocation from a cytosol to a membrane surface is one of the stages of regulation of the amount of LO catalysis products in the cell. A sorption to the membrane surface is described for most LOs from plant and animal sources. This review presents the data about regulation of the LO activity by the lipid compounds – both natural and chemically modified. Lipids might regulate the LO activity through: protein-lipid interactions of C2 domain with the membrane, changes in the enzyme affinity, the LOs translocation, allosteric regulation, increase in the selectivity towards substrates. The regulatory effect of active compound on the enzyme activity depends on the lipophilicity of effectors. Considering the LO activity it is necessary to take into account the enzyme microenvironment and its influence on the range of the LO products.